Prospective cardiac MRI for the analysis of biventricular function in children undergoing cancer treatments. Issue 5 (16th January 2015) - de Ville de Goyet, Maëlle; Brichard, Benedicte; Robert, Annie; Renard, Laurette; Veyckemans, Francis; Vanhoutte, Laetitia; Moniotte, Stephane
Abstract : Background: Cardiotoxicity is one of the most serious long‐term complications in childhood cancer survivors. Measurement of the left ventricular ejection and shortening fraction remains the most common screening tool for cardiac systolic dysfunction. However, M‐mode echocardiography can be viewed as a crude approach as refined strategies are now available. The aim of this prospective study was to determine the role of cardiac MRI in the detection of subclinical left or right ventricular dysfunction as well as the prevalence of myocardial scaring in patients undergoing cancer treatments. Procedure: Eighty‐one children were enrolled in a pre‐chemotherapy and then in a yearly protocol including a: (i) clinical evaluation; (ii) laboratory evaluation; (iii) electrocardiogram; (iv) echocardiogram; and (v) a cardiac magnetic resonance imaging (cMRI). Results: Early left ventricular systolic dysfunction was only detected in two patients. The entire cohort presented a significant increase of the left atrial volume as measured by cMRI. This finding correlated with the total cumulative dose of anthracyclines (r = 0.34; P  < 0.05) and the mean left ventricular radiation dose (r = 0.86; P  < 0.05). We also observed a mild increase of myocardial scaring, similarly correlated to the radiation dose (r = 0.85; P  < 0.05). Conclusions: Screening tools for late‐onset cardiomyopathy secondary to cancer treatment are lacking. Our findings support the use of cMRI for the evaluation of the left atrial volume, as an early marker of diastolic dysfunction, and myocardial delayed enhancement, as a marker of myocardial fibrosis and scaring. Longer follow‐up and larger studies are still needed to better define the role of cMRI in the evaluation of childhood cancer survivors. Pediatr Blood Cancer 2015;62:867–874. © 2015 Wiley Periodicals, Inc.